eval_uasi Pemasangan LBSM Loopring untuk Menurunkan SAIDI pada Penyulang PKR 16 dan Riyal di Wilayah Kerja ULP Pulung Kencana - Masta, Putra Fikrianda; Syofian, Andi; Anugrah, Anggun; Warmi, Yusreni; Dewi, Arfita Yuana (ARZUSIN, 2024)
The reliability and continuity of electric power supply are heavily reliant on the maneuverability of existing feeders. To enhance this capability, the installation of LBSM (Load Break Switch Motorized) devices is essential for feeders lacking the ability to maneuver to alternative feeders. This LBSM installation will be implement on the Riyal and PKR 16 feeders at ULP Pulung Kencana. The Riyal feeder receives power from the Mesuji Substation, while the PKR 16 feeder is supplied by the Pakuon Ratu Substation. Both feeders currently lack switches for maneuvering in the event of disturbances or maintenance, which significantly contributes to high SAIDI (System Average Interruption Duration Index) rates. To determine the optimal installation points for the LBSM, a thorough analysis was conducted, prioritizing the closest proximity between the two feeders and incorporating topologic calculations using the Digsilent PowerFactory 15.1 software. This approach ensures optimal performance of the distribution network. The installation of the LBSM loopring is anticipated to significantly improve network maneuverability, thereby reducing the SAIDI rates at ULP Pulung Kencana.